The contrasting responses of abundant and rare microbial community structures and co-occurrence networks to secondary forest succession in the subalpine region - Zhang, Xiaoying; Zhao, Wenqiang; Kou, Yongping; Fang, Kai; Liu, Yanjiao; He, Heliang; Liu, Qing (Frontiers in Microbiology, 2023)
Knowledge of variations in abundant and rare soil microbial communities and interactions during secondary forest succession is lacking. Soil samples were gathered from different secondary successional stages (grassland, shrubland, and secondary forest) to study the responses of abundant and rare bacterial and fungal communities, interactions and driving factors to secondary forest succession by Illumina sequencing of the 16S and ITS rRNA genes. The results showed that the α-diversities (Shannon index) of abundant bacteria and fungi revealed no significant changes during secondary forest succession, but increased significantly for rare bacteria. The abundant and rare bacterial and fungal β-diversities changed significantly during secondary forest succession. Network analysis showed no obvious changes in the topological properties (nodes, links, and average degree) of abundant microbial networks during secondary forest succession. In contrast,, these properties of the rare microbial networks in the secondary forest were higher than those in the grassland and shrubland, indicating that rare microbial networks are more responsive to secondary forest succession than abundant microorganisms. Additionally, rare microbial networks revealed more microbial interactions and greater network complexity than abundant microbial networks due to their higher numbers of nodes and links. The keystone species differed between the abundant and rare microbial networks and consisted of 1 and 48 keystone taxa in the abundant and rare microbial networks, respectively. Soil TP was the most important influencing factor of abundant and rare bacterial communities. Successional stages and plant richness had the most important influences on abundant and rare fungal communities, respectively. C:P, SM and N:P were mainly related to abundant and rare microbial network topological properties. Our study indicates that abundant and rare microbial communities, interactions and driving factors respond differently to secondary forest succession.